Sexuality, Society & Pedagogy - Francis, Dennis A. (UJ Press, 2014)
Sexuality, Society and Pedagogy problematises some of the prevailing assumptions that frame this area of study. In doing so, it aims to make visible the challenges of teaching sexuality education in South African schools, while demonstrating its potential for reshaping our conceptions of the social and cultural representations thereof. Although the book is largely situated in experiences and perspectives within the South African context, it is hoped that the questions raised, reflections, analyses and arguments will contribute to thinking about sexuality education in diverse contexts, in particular more developing contexts.